2001
DOI: 10.1029/2000jd900758
|View full text |Cite
|
Sign up to set email alerts
|

April 1998 Asian dust event: A southern California perspective

Abstract: Abstract. In late April 1998 an extreme Asian dust episode reached the U.S. western seaboard. This event was observed by several in situ and remote sensing atmospheric measurement stations. Dramatic reductions in boundary layer visibility were recorded and the resultant peak backscatter coefficients exceeded prevailing upper tropospheric background conditions by at least 2 orders of magnitude. An analysis of this event is given using lidar vertical backscatter profilometry, concurrent Sun photometer opacity da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
62
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(69 citation statements)
references
References 25 publications
7
62
0
Order By: Relevance
“…This is caused by the transport of the TSP due to dust storms. Recent studies indicate that dust storms originated in the East Asia not only influence air pollution in the origins and their neighboring regions Murayama et al, 2001;Sun et al, 2001;Zhou et al, 2002), but also have a long-distance effect across Pacific by atmospheric circulation (Husar et al, 2001;Tratt et al, 2001;Sun et al, 2001;Laat et al, 2001;Clarke et al, 2001). The major sources of the dust storms are the Gobi desert in Mongolia and northern China and Taklimakan desert in western China (Sun et al, 2001).…”
Section: Dust Stormsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is caused by the transport of the TSP due to dust storms. Recent studies indicate that dust storms originated in the East Asia not only influence air pollution in the origins and their neighboring regions Murayama et al, 2001;Sun et al, 2001;Zhou et al, 2002), but also have a long-distance effect across Pacific by atmospheric circulation (Husar et al, 2001;Tratt et al, 2001;Sun et al, 2001;Laat et al, 2001;Clarke et al, 2001). The major sources of the dust storms are the Gobi desert in Mongolia and northern China and Taklimakan desert in western China (Sun et al, 2001).…”
Section: Dust Stormsmentioning
confidence: 99%
“…The major sources of the dust storms are the Gobi desert in Mongolia and northern China and Taklimakan desert in western China (Sun et al, 2001). In April 1998, an Asian dust storm proceeded eastward with the west wind across Pacific Ocean and subsided to the surface along the mountain ranges between British Columbia and California (Husar et al, 2001;Tratt et al, 2001;Vaughan et al, 2001). Other reports indicated that there is a positive correlation between dust storm in Hexi Corridor and air pollution in Lanzhou Ding et al, 2001).…”
Section: Dust Stormsmentioning
confidence: 99%
“…Asian dust can be transported over the North Pacific Ocean and reach Midway and North America (Duce et al, 1980;Shaw, 1980;Betzer et al, 1988;Clarke et al, 2001;Husar et al, 2001;Tratt et al, 2001;Huang et al, 2008;Eguchi et al, 2009;Su and Toon, 2009). Asian dust also can be transported over global scales Grousset et al, 2003;Uno et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The mineral particles are then transported to Northeastern Asia and usually result in serious deterioration in local air quality (e.g., Iwasaka et al 1983;Hursar et al 2001;Murayama et al 2001;Kim et al 2003). Sometimes, Asian dust transport can even be observed in the North Pacific Ocean and North America (e.g., Duce et al 1980;Shaw 1980;Uematsu et al 1983;Jaffe et al 1999;Mckendry et al 2001;Tratt et al 2001;VanCuren and Cahill 2002). Although the Asian dust particles are carried mostly by westerly winds and spread over the mid-latitudes, a portion of the dust particles can also be transported to Taiwan under the prevailing northeasters of the winter monsoon.…”
Section: Introductionmentioning
confidence: 99%